The design and implementation of a QR-code enabled mobile online judging application - Mohd Nor, Rizal; Muhd Ridzuan, Abdulfattah Muhyideen; Mohamed Razi, Mohamed Jalaldeen (IEEE, 2014)
In this paper, we show the design considerations of using QR code in the evaluation of academic poster presentations. Most researchers focused their study in the usability and implementation of a QR-code in mobile applications. While its use and implementation can be applied to many areas, its adoption is still at an infant stage. This is due to poor design considerations which affects users satisfaction and ease of use. In our research, we designed and developed a mobile online judging application called MOJA to be used by judges in the IIUM IRIIE 2014 poster exhibition and performed a survey to measure user’s satisfaction in using the application. Our results show that most of the users are satisfied with MOJA based on their perceived usefulness of our application in their judging process. Additionally, we showed that their perceived ease of use influenced users to use MOJA in their future judging process, as well as, their willingness to recommend MOJA to their friends and colleagues.